Corn productivity and profitability in raised stale seedbed systems with and without cover crops. Issue 1 (23rd February 2022) - Spencer, Gene Dave; Krutz, Larry Jason; Locke, Martin; Gholson, Drew M.; Bryant, Corey; Mills, Brian E.; Henry, William Brien; Golden, Bobby
Abstract: Cover crops are promoted for reducing the negative environmental effects of high‐input row‐crop production; however, cover crop adoption in the mid‐southern United States is low, partly because of a perceived increase in risk. The objective of this research was to determine if cover crops cost‐effectively improved the productivity and water use of corn ( Zea mays L.) in raised stale seedbed systems. The effects of four cover crops, namely Austrian winter pea [ Pisum sativum var. arvense (L.) Poiret], crimson clover ( Trifolium incarnatum L.), cereal rye ( Secale cereal L.), and tillage radish ( Raphanus sativus L.), in a raised stale seedbed environment on corn grain yield, net returns, and water use efficiency (WUE) were investigated at Stoneville, MS, on a Commerce very fine sandy loam soil (fine‐silty, mixed, superactive, nonacid, thermic Fluvaquentic Endoaquept). A cover crop preceding corn maintained or decreased yield, net returns, and WUE. Cover crops had no effect on corn grain yield in any year, except for 2017, in which Austrian winter pea and cereal rye decreased yield by 37 and 45%, respectively. Tillage radish never affected net returns; however, the inclusion of Austrian winter pea, crimson clover, or cereal rye reduced net returns by up to 57% in two of four years. Cover crops either maintained or decreased WUE by up to 44%. In the 4 yr of this research, the inclusion of a cover crop in a raised stale seedbed system only maintained or decreased corn grain yield, net returns, and WUE. Core Ideas: After 4 yr of cover cropping, there were no measured benefits. Two cover crops reduced corn grain yield in Year 1; otherwise, no yield differences were seen. Cover crop had no effect or decreased net returns by up to 57%. Cover crop had no effect or decreased water use efficiency by up to 44%.